Simulation of the hydrolytic degradation of irradiated PLGA - Quek, Jing Yu. (2009)
With the increase in usage of PLGA in biomedical applications, especially in controlled drug delivery, it is important to understand and be able to manipulate the degradation rate of PLGA. Several studies had been conducted to understand the effects of irradiation on PLGA and the hydrolytic degradation of the polymer. This project proposes a simulation that uses mathematical modeling based on the binary tree model combined with population balance modeling to simulate the hydrolytic degradation of irradiated PLGA 80:20 at 20Mrad. The objective of this project is to provide a simulation program that can be used to verify experimental results and at the same time predict the hydrolytic degradation of PLGA without conducting costly and time consuming experiments. The results of the simulation were proven to correspond closely with experimental results, hence proving the ability of the simulation program to simulate the degradation of PLGA. In order to better describe the initial distribution of the simulation, the normal distribution and the Flory distribution were chosen to simulate the initial distribution in comparison with available experimental results for their suitability.